The prognostic value of blood pH and lactate and metformin concentrations in severe metformin-associated lactic acidosis - Kajbaf, Farshad; Lalau, Jean-Daniel (BMC Pharmacology and Toxicology, 2013)
Analysis of the prognostic values of blood pH and lactate and plasma metformin concentrations in severe metformin-associated lactic acidosis may help to resolve the following paradox: metformin provides impressive, beneficial effects but is also associated with life-threatening adverse effects.